2005
DOI: 10.1016/j.nimb.2005.07.235
|View full text |Cite
|
Sign up to set email alerts
|

Idaho Explosives Detection System

Abstract: The Idaho Explosives Detection System (IEDS) was developed at the Idaho National Laboratory (INL) to respond to threats imposed by delivery trucks carrying explosives into military bases. A full-scale prototype system has been built and is currently undergoing testing. The system consists of two racks, one on each side of a subject vehicle. Each rack includes a neutron generator and an array of NaI detectors. The two neutron generators are pulsed and synchronized. A laptop computer controls the entire system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Neutron systems are employed to detect and analyze chemical compounds and explosive threats (Vourvopoulos and Womble, 2001;Gozani, 2004;Strellis et al, 2009;Eleon et al, 2010). In addition, they are utilized in vehicle-and cargo-scanning scenarios (Barzilov and Womble, 2003;Reber et al, 2005;Perret et al, 2006;Koltick et al, 2007) as well as humanitarian de-mining and confirmation of unexploded ordnance (Aleksandrov et al, 2005;Lanza, 2006;Barzilov and Womble, 2014). Neutron methods are studied for in situ astrochemistry missions (Parsons et al, 2012) and terrestrial soil analysis (Wielopolski et al, 2008), for in vivo cancer diagnostics (Maglich and Nalcioglu, 2010), and in medical studies of human body composition (Shypailo and Ellis, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Neutron systems are employed to detect and analyze chemical compounds and explosive threats (Vourvopoulos and Womble, 2001;Gozani, 2004;Strellis et al, 2009;Eleon et al, 2010). In addition, they are utilized in vehicle-and cargo-scanning scenarios (Barzilov and Womble, 2003;Reber et al, 2005;Perret et al, 2006;Koltick et al, 2007) as well as humanitarian de-mining and confirmation of unexploded ordnance (Aleksandrov et al, 2005;Lanza, 2006;Barzilov and Womble, 2014). Neutron methods are studied for in situ astrochemistry missions (Parsons et al, 2012) and terrestrial soil analysis (Wielopolski et al, 2008), for in vivo cancer diagnostics (Maglich and Nalcioglu, 2010), and in medical studies of human body composition (Shypailo and Ellis, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Security applications of neutron based systems are for chemical and explosive threats detection (Vourvopoulos & Womble, 2001;Aleksandrov et al, 2005;Lanza, 2006), including the search for threats in cargo containers (Barzilov & Womble, 2003) and vehicles (Reber et al, 2005;Koltick et al, 2007), humanitarian demining and confirmation of unexploded ordinance (Womble et al, 2002;Holslin et al, 2006). Such technologies are considered in astrochemistry applications for in situ analysis of planetary samples (Parsons et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[18] Cester et al have shown an alternative approach for combining multiple active interrogation signatures, merging time correlated data from an associated-particle ENG with gammaray spectroscopy.. [19] Research and development activities exploring the practical applications of active interrogation, using radioisotope neutron sources, ENGs, and high-energy bremsstrahlung sources have been underway at Idaho National Laboratory (INL) for over two decades. [20][21][22][23] This prior work has explored the use of active interrogation methods for detecting and characterizing toxic industrial chemicals, narcotics, chemical warfare materiel, currency, high explosives, and special nuclear material (SNM). In this paper we report the results of a recently completed simulation and modeling campaign exploring the utility of portable ANI methodologies for detecting shielded HEU.…”
Section: Introductionmentioning
confidence: 99%